From screen to scene: exploring factors influencing flow state and actual destination visitation tendencies in short travel videos - Chong, Sin-Er; Lim, Xin-Jean; Cheah, Jun-Hwa; Tee, Keng Kok (Routledge, 2024)
The landscape of travel information dissemination has evolved, with short travel video (STV) content now taking centre stage. While existing studies have explored the role of STVs in promoting destinations, there is still a need to pinpoint which elements of this marketing approach resonate most strongly with audiences. Our research, grounded in the S-O-R framework and flow theory, examines how technological, destination-related, and individual factors act as catalysts for immersive viewing experiences and subsequent desire to explore featured destinations. We employed a dual analytical approach: PLS-SEM to map relationships between core concepts, and NCA to identify critical factors for maximising outcomes. The study found that perceived ease of use, destination brand authenticity, destination trust, present hedonism, and price reasonableness positively influence audience flow states while watching STVs. Moreover, the tendency to visit actual sites is heightened when the flow state experience is increased. This underscores the importance of considering these factors as crucial stimuli when exploring the effectiveness of STVs in shaping audience emotional states and responses.